Current perspectives on pharmacist home visits: do we keep reinventing the wheel? - Flanagan PS; Barns A (Dove Medical Press, 2018)
Priti S Flanagan,1,2 Andrea Barns1 1Pharmacy Community Programs, Lower Mainland Pharmacy Services, Langley, BC, Canada; 2Faculty of Pharmaceutical Sciences, University of British Columbia, Vancouver, BC, Canada Abstract: The scope of clinical pharmacy services available in outpatient settings, including home care, continues to expand. This review sought to identify the evidence to support pharmacist provision of clinical pharmacy services in a home care setting. Seventy-five reports were identified in the literature that provided evaluation and description of clinical pharmacy home visit services available around the world. Based on results from randomized controlled trials, pharmacist home visit interventions can improve patient medication adherence and knowledge, but have little impact on health care resource utilization. Other literature reported benefits of a pharmacist home visit service such as patient satisfaction, improved medication appropriateness, increased persistence with warfarin therapy, and increased medication discrepancy resolution. Current perspectives to consider in establishing or evaluating clinical pharmacy services offered in a home care setting include: staff competency, ideal target patient population, staff safety, use of technology, collaborative relationships with other health care providers, activities performed during a home visit, and pharmacist autonomy. Keywords: clinical pharmacy, home care, home visit, medication review, pharmacist